Measurement of peak expiratory flow rate values in healthy school going children between 6 and 12 years attending urban schools in Chennai - Durairaj, Prabakar; Raju, Sasivarathan; Thirumalaikumarasamy, Sivaraman (International Journal of Contemporary Pediatrics, 2017)
Background: Peak expiratory flow rate (PEFR) is an important tool in monitoring patient’s changes in asthma. Bronchial asthma is among the commonest disorders in childhood. Here authors planned to measure PEFR in healthy school going children between 6 and 12 years and correlate PEFR against various parameters such as height, weight, sex, age and chest circumference. Methods: The study was conducted from February 2005-August 2006 among healthy children between 6 and 12 years of age attending urban schools of both sexes in Chennai. The schools were selected randomly. Results: PEFR values were measured in a large number of children between 6 and 12 years and varied significantly between boys and girls in the age group 6 to 12 years. Among all the study variables, height had shown the maximum positive correlation to PEFR in both boys and girls. The co-efficient of regression derived for height was found to be highly statistically significant both in boys and girls. Conclusions: Significant correlations were found between PEFR and biological variables like age, weight, height and chest circumference. The correlation is more robust with regard to height. Boys have more PEFR values than girls across all age groups.